Pelaksanaan Pembelajaran Band Di Kelas XI Jurusan Seni Musik Populer SMK Negeri 7 Padang - Farlino Tanjung, Vadrick; Yensharti, Yensharti (FBS Universitas Negeri Padang, 2022)
This study aims to describe the implementation of Band learning in class XI students of the Department of Art Popular Music at SMK Negeri 7 Padang. This type of research is a qualitative descriptive study, with the object of research namely Band learning in class XI students of the Department of Art Popular Music at SMK Negeri 7 Padang. The main instrument in this study was the researcher himself, assisted by supporting instruments in the form of notebooks and mobile phones. Data collection techniques were carried out through library research, observation, interviews, and documentation. The analysis technique is through the steps of data reduction, data presentation, analysis, and concluding. Based on the results of the study, it was found that Band learning in class XI of the Department of Art Popular Music was not running optimally, due to the lack of seriousness of students in carrying out the tasks given by the teacher, even though the implementation of learning carried out by the teacher was following the Learning Implementation Plan (RPP). Factors that cause Band learning are not optimal because students do not have personal instruments, limited lesson hours during the pandemic, and lack of student motivation.